The effect analysis of three-dimensional divergence and its vertical gradient on convection initiation - Zhou, Kuo; Ran, Lingkun; Zhang, Wancheng; Tian, Liqing; Chen, Lei; Liu, Haiwen (Frontiers in Earth Science, 2023)
A severe convection process occurred in southern Xinjiang during June 15-17, 2021. Here, the convection initiation mechanism is revealed by analyzing the impacts of three-dimensional divergence on the changes in pressure and the vertical pressure gradient force (VPGF). The pressure tendency equation and vertical pressure gradient force equation are derived based on three-dimensional divergence. It is shown that three-dimensional divergence has a better correlation with precipitation. The local change in pressure is affected mainly by the three-dimensional divergence forcing term. The air mass accumulates in the lower layers because of the three-dimensional convergence in the windward slope, strengthening the positive pressure change tendency. Three-dimensional convergence in the lower layers converts to divergence with height, leading to air mass loss in the upper layers. The air mass redistributes vertically owing to the positive vertical gradient of three-dimensional divergence, which motivates the upward VPGF. The local change in VPGF is highly correlated with the vertical velocity. The vertical velocity increases as the upward VPGF strengthens, resulting in convection initiation in southern Xinjiang.